Gregorio Vásquez de Arce y Ceballos (1638–1711) in Viceregal Colombia: Workshop Practices and the Role of Draftsmanship - Brown, Michael (RACAR : Revue d'art canadienne / Canadian Art Review, 2013)
The Colombian painter Gregorio Vásquez de Arce y Ceballos (1638–1711) was born in Bogotá to a family who had come from Seville in southern Spain at the end of the sixteenth century. By Vásquez’s lifetime, Bogotá had become one of the most important artistic centres in the Spanish viceroyalty of New Granada, which spanned from present-day Ecuador and Colombia northward to Panamá and Venezuela. In the context of the history of art in the Spanish viceroyalties, Vásquez stands out for a number of reasons, perhaps most notably for his extant corpus of drawings, of which at least 106 sheets survive. He was also among the most prolific painters in the three-century history of Spain’s American colonies. Best known for his work for various religious institutions in Bogotá, Tunja and elsewhere in New Granada, Vásquez’s most important commission was perhaps for the dozens of paintings that decorate the Sagrario Chapel, which was constructed between 1660 and 1700 and sits adjacent to the cathedral in Bogotá. Vásquez’s enormous artistic production was made possible by a workshop that appears to have included his brother, daughter and son. A small group of paintings has recently come to light in the Denver Art Museum, here attributed to Gregorio Vásquez and his workshop, which provide new insight into this great painter’s studio practices and teaching methods, including the prominent role played by European prints and the master’s own drawings.